Childhood adverse life events and parental psychopathology as risk factors for bipolar disorder - Bergink, V (Transl Psychiatry, 2016)
Childhood adverse events are risk factors for later bipolar disorder. We quantified the risks for a later diagnosis of bipolar disorder after exposure to adverse life events in children with and without parental psychopathology. This register-based population cohort study included all persons born in Denmark from 1980 to 1998 (980 554 persons). Adversities before age 15 years were: familial disruption; parental somatic illness; any parental psychopathology; parental labour market exclusion; parental imprisonment; placement in out-of-home care; and parental natural and unnatural death. We calculated risk estimates of each of these eight life events as single exposure and risk estimates for exposure to multiple life events. Main outcome variable was a diagnosis of bipolar disorder after the age of 15 years, analysed with Cox proportional hazard regression. Single exposure to most of the investigated adversities were associated with increased risk for bipolar disorder, exceptions were parental somatic illness and parental natural death. By far the strongest risk factor for bipolar disorder in our study was any mental disorder in the parent (hazard ratio 3.53; 95% confidence interval 2.73–4.53) and the additional effects of life events on bipolar risk were limited. An effect of early adverse life events on bipolar risk later in life was mainly observed in children without parental psychopathology. Our findings do not exclude early-life events as possible risk factors, but challenge the concept of adversities as important independent determinants of bipolar disorder in genetically vulnerable individuals.